Pengaruh CEO Narcissism, Financial Distress, Company Size, dan Green Accounting terhadap Tax Avoidance - Ardiana Salsabila Putri; Dirvi Surya Abbas; Imam Hidayat (Owner : Riset dan Jurnal Akuntansi, 2025)
Taxes are the largest source of revenue in Indonesia, prompting some companies to engage in tax avoidance. This study aims to examine and obtain empirical evidence regarding the influence of CEO narcissism, financial distress, company size, and green accounting on tax avoidance. The research population consists of manufacturing companies from 2019-2023 that are listed on the Indonesia Stock Exchange or the official website of the company being studied. This study uses a quantitative approach with secondary data. The study uses the Eviews 12 application to manage the data. The data collection technique used is purposive sampling with 65 data samples. Additionally, the data analysis technique used is moderation regression analysis with hypothesis testing using the t-test. The research findings conclude as follows: (1) CEO narcissism has a negative impact on tax avoidance, (2) financial distress do not have an impact on tax avoidance, (3) company size does not have an impact on tax avoidance, (4) green accounting does not have an impact on tax avoidance in manufacturing companies